The Perceptions of English Students' Reading Strategies at University Level - Ahmad Qusyaeri; Rasyidah Nur Aisyah; Ana Ahsana El-Sulukiyyah (Penerbit STKIP PGRI Bangkalan, 2021)
Reading needs an appropriate strategy to get out the point of the passage effectively. This research aimed to investigate the English students’ perceptions of their reading strategies at PGRI Wiranegara University. The purpose of this research was to describe the students’ perception about reading strategies and finding the highest and the lowest scores of reading strategies. Type of this research was descriptive quantitative research. The research subjects were English students at PGRI Wiranegara University Pasuruan. In this research, the researcher used modified version of Survey of Reading Strategies (SORS) by Mokhtari and Sheorey (2002) which presented 35 statements of reading strategies, while the method of analyzing data used Likert scale and SPSS. The result of this research showed that most students were accustomed to apply reading strategies presented in the questionnaire form. Besides, this strategy “When text becomes difficult, I read slowly and carefully” was the highest score, and “I analyze the structure early to help me in understanding” was the lowest score.